2011
DOI: 10.1016/j.jelekin.2011.08.013
|View full text |Cite
|
Sign up to set email alerts
|

Anticipatory postural adjustments in children with hemiplegia and diplegia

Abstract: Anticipatory postural adjustments (APAs) play an important role in the performance of many activities requiring the maintenance of standing posture. However, little is known about if and how children with cerebral palsy (CP) generate APAs. Two groups of children with CP (hemiplegia and diplegia) and a group of children with typical motor development performed arm flexion and extension movements while standing on a force platform. Electromyographic activity of six trunk and leg muscles and displacement of cente… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
41
0
1

Year Published

2012
2012
2022
2022

Publication Types

Select...
8
2

Relationship

1
9

Authors

Journals

citations
Cited by 59 publications
(44 citation statements)
references
References 52 publications
2
41
0
1
Order By: Relevance
“…For example, children with cerebral palsy have demonstrated deficits in anticipatory mechanisms (feedforward postural adjustments) [14][15][16][17][18], adaptive mechanisms (feedback postural adjustments) [3,14,[19][20][21], musculoskeletal systems (muscle force and range of motion required for standing balance) [22] and sensory systems (visual and proprioceptive function required for balance) [23,24]. This research illustrates well how one population can experience a broad range of postural control problems, and also that there is an absence of a comprehensive clinical assessment for children.…”
Section: Introductionmentioning
confidence: 99%
“…For example, children with cerebral palsy have demonstrated deficits in anticipatory mechanisms (feedforward postural adjustments) [14][15][16][17][18], adaptive mechanisms (feedback postural adjustments) [3,14,[19][20][21], musculoskeletal systems (muscle force and range of motion required for standing balance) [22] and sensory systems (visual and proprioceptive function required for balance) [23,24]. This research illustrates well how one population can experience a broad range of postural control problems, and also that there is an absence of a comprehensive clinical assessment for children.…”
Section: Introductionmentioning
confidence: 99%
“…However, the EMG amplitudes of MH and GcM in the background range were not smaller in the SDCP group than in the control group, although these values were not normalized. A previous study reported that individuals with SDCP exhibit greater background activity before voluntary arm movement than individuals without disability (Girolami et al 2011). It is thus unlikely that the lack of anticipatory inhibition of dorsal lower limb muscles in the SDCP group was due to muscle activities in the background range.…”
Section: Discussionmentioning
confidence: 84%
“…This is clearly related to the fact that children must be able to perform certain tasks independently so that these studies can be carried out. This classification was based either on GMFCS levels (Burtner, Woollacott, Craft, & Roncesvalles, 2007; Chen & Woollacott, 2007; Corrêa et al, 2007; Girolami, Shiratory, & Aruin, 2011; Ju et al, 2012; Liu, Zaino, & McCoy, 2007; Reilly, Woollacott, & Donkelaar, 2008; Rha, Kim, & Park, 2010; Saavedra et al, 2010; Zaino & McCoy, 2008) or other criteria, such as topography of the lesion (Barela et al, 2011; Bigongiari et al, 2011; Burtner, Qualls, & Woollacott, 1998; Cherng, Su, Chen, & Kuan, 1999; Liao, Jeng, Lai, Cheng, & Hu, 1997; Rose et al, 2002). …”
Section: Resultsmentioning
confidence: 99%